Effect of spinal anesthesia-induced deafferentation on pain processing in healthy male volunteers: A task-related fMRI study - Sitsen, Elske; Khalili-Mahani, Najmeh; de Rover, Mischa; Dahan, Albert; Niesters, Marieke (Frontiers in Pain Research, 2022)
Background: Spinal anesthesia causes short-term deafferentation and alters the cross-talk among brain regions involved in pain perception and pain modulation. In the current study, we examined the effect of spinal anesthesia on pain sensitivity of noxious thermal stimuli in non-deafferented skin areas using a functional magnetic resonance imaging (fMRI) paradigm. Methods: Twenty-two healthy subjects participated in the study. We performed a task-based fMRI study using a randomized crossover design. Subjects were scanned at two-time points: before and after spinal anesthesia or a control condition (T1 and T2) Spinal anesthesia resulted in sensory loss up to dermatome Th6. Calibrated heat-pain stimuli were administered to the right forearm (C8-Th1) using a box-car design (blocks of 10s on/25s off) during MRI scanning. To account for interindividual differences in pain sensitivity, we computed a compound variable (pain score/maximum tolerated temperature perceived during calibration). We tested a general linear model to examine the effects of treatment (spinal vs. control) while accounting for time (T1 vs. T2), and pain/temperature ratio. Results: The pain scores (range 0 to 100 mm) before and after the scans were (mean ± SD) 56 ± 18 mm and 54 ± 19 mm in the control session, and 51 ± 15 mm and 59 ± 15 mm in the spinal anesthesia session. The mean pain ratio was significantly greater for the spinal anesthesia condition compared to the control condition. Independent of treatment, noxious stimuli caused significant activation in the precentral and postcentral gyrus and superior frontal gyrus, and deactivation in the precuneus cortex, cerebellum, inferior parietal lobule and superior frontal gyrus. Compared to control, noxious thermal stimuli significantly increased activation of the bilateral inferior parietal lobule and deactivation in bilateral postcentral and precentral gyrus in the presence of spinal anesthesia. Conclusions: Spinal anesthesia had a significant impact on brain regions involved in somatosensory and cognitive processing of noxious afferent input. The loss of sensory and motor activity caused by spinal anesthesia resulted in small alterations in pain sensitivity in non-deafferented skin regions, i.e. at dermatomes above the level of the spinal anesthetic, as well as significant modification of central pain processing.